1995
DOI: 10.1083/jcb.131.5.1231
|View full text |Cite
|
Sign up to set email alerts
|

Ezrin oligomers are major cytoskeletal components of placental microvilli: a proposal for their involvement in cortical morphogenesis.

Abstract: Abstract. Ezrin is a component of the microvillus cytoskeleton of a variety of polarized epithelial cells and is believed to function as a membrane-cytoskeletal linker. In this study, we isolated microvilli from human placental syncytiotrophoblast as a model system for biochemical analysis of ezrin function. In contrast to intestinal microvilli, ezrin is a major protein component of placental microvilli, comprising ~5 % of the total protein mass and present at about one quarter of the molar abundance of actin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
173
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(187 citation statements)
references
References 64 publications
14
173
0
Order By: Relevance
“…In contrast, ezrin, a protein that is known to self-associate, demonstrated the presence of oligomers under similar conditions (supplemental Fig. S2B) (33). Together these studies demonstrate the ability of villin to self-associate and further suggest that this property of villin may not be shared by all proteins of its family.…”
Section: Villin Can Bundle Actin Filament Using a Single F-actinmentioning
confidence: 72%
“…In contrast, ezrin, a protein that is known to self-associate, demonstrated the presence of oligomers under similar conditions (supplemental Fig. S2B) (33). Together these studies demonstrate the ability of villin to self-associate and further suggest that this property of villin may not be shared by all proteins of its family.…”
Section: Villin Can Bundle Actin Filament Using a Single F-actinmentioning
confidence: 72%
“…4B). Ezrin eluted mainly in two peaks, a higher-MW peak (Ն232,000), most likely containing oligomers (18), and an extended, lower-MW peak Ͼ67,000. Moesin had a similar elution pattern (not shown).…”
Section: Phosphorylated Erm Proteins Form Distinct Complexes With Ebp50mentioning
confidence: 99%
“…The membrane-cytoskeleton linker ezrin is mainly expressed in epithelial cells where it associates to the apical actin-rich structures such as microvilli (Berryman et al, 1993(Berryman et al, , 1995. Recent genetic analyses revealed that ezrin is essential for the morphogenesis of epithelial cells (Fiévet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%